Association between Glycosylated Hemoglobin on Outcome of Patient with Acute Ischemic Stroke Treated with Thrombolysis - Ali, Mohammad Yousuf; Rahman, Aminur; Paul, Bikash Chandra; Hoque, Syed Md Asadul; Zakia, Kazi Ismat (Sir Salimullah Medical College Journal, 2025)
Background: Elevated glycated haemoglobin (HbA1c) levels have been associated with poor outcomes in stroke patients, but evidence of its impact on the efficacy of intravenous thrombolysis (IVT) remains conflicting. This study aimed to evaluate the impact of admission glycemic status, as reflected by HbA1c, on clinical outcomes following IVT in acute ischemic stroke. Methods: This single-center cohort study was conducted at National Institute of Neurosciences & Hospital (NINS) from January 2024 to December 2024 included 118 hyperacute ischemic stroke patients treated with intravenous thrombolysis using rtPA. Baseline demographics, comorbidities, NIHSS, and laboratory parameters including HbA1c were recorded. Patients were stratified into normal, prediabetic, and diabetic groups based on HbA1c. Outcomes were assessed by NIHSS at 24 hours and Day 7, and by mRS on Day 7. Statistical analyses included Chi-square tests, multinomial, and binary logistic regression to evaluate predictors of outcome. Results: The study was predominantly male (73.7%) with a mean baseline NIHSS of 9.43±3.905. Prediabetic and diabetic patients had significantly poorer neurological improvement compared to normal HbA1c patients, in 59.1% vs. 75% of cases (p=0.035) and 52.9% vs. 75% of cases (p=0.035), respectively. Multinomial regression analysis revealed that for every 1% increase in HbA1c, odds of stable vs. improved outcome were increased by 30% (OR=1.30, p=0.034) and worsened vs. improved outcome by 72% (OR=1.72, p=0.005). Age and baseline NIHSS were also independent predictors of outcome, while hypertension was not significantly related. Conclusion: Elevated HbA1c levels are independently related to poor neurological outcomes following IVT in acute ischemic stroke. HbA1c may serve as a valuable prognostic marker to identify those patients at higher risk of unfavourable response to thrombolytic therapy. Sir Salimullah Med Coll J 2024; 32: 52-58